2012
DOI: 10.1007/s12640-012-9328-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Role of the Isoflavone Diadzein in Lipopolysaccharide-Stimulated Microglia: Implications for Parkinson’s Disease

Abstract: Microglial activation and subsequent release of toxic pro-inflammatory factors are believed to play an important role in neuronal cell death associated with Parkinson’s disease (PD). Compounds that inhibit microglia activation and suppress pro-inflammatory factor release have been reported to have neuroprotective effects in animal models of PD. In this study, we tested whether diadzein, a natural isoflavone found in soybean, attenuated lipopolysaccharide (LPS)-induced release of inflammatory mediators in BV-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 37 publications
(42 reference statements)
0
43
0
1
Order By: Relevance
“…Daidzein pretreatment was found to significantly suppress LPS-induced mRNA expression of the pro-inflammatory factors nitric oxide and IL-6 in murine microglial cells, which suggests the neuroprotective properties of daidzein [28] . Release of soluble pro-inflammatory factors appears to be via inhibition of oxidative induction and activation of the p38 MAP kinase-NF-κB pathway [28] .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Daidzein pretreatment was found to significantly suppress LPS-induced mRNA expression of the pro-inflammatory factors nitric oxide and IL-6 in murine microglial cells, which suggests the neuroprotective properties of daidzein [28] . Release of soluble pro-inflammatory factors appears to be via inhibition of oxidative induction and activation of the p38 MAP kinase-NF-κB pathway [28] .…”
Section: Discussionmentioning
confidence: 84%
“…Release of soluble pro-inflammatory factors appears to be via inhibition of oxidative induction and activation of the p38 MAP kinase-NF-κB pathway [28] . Another study showed that daidzein significantly inhibited the production of NO and IL-6 and decreased the mRNA expression of NOS and IL-6 in LPS-treated RAW264.7 cells; however, the JNK and p38 pathways were not involved in daidzein-mediated suppression of NF-κB-mediated transcription [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have used BV2 cells to demonstrate the role of microglia in neuroinflammation [4, 6, 7, 34]. In our study we used the BV2 cells to alter RNF11 levels since primary microglial cultures resist transfection or transduction protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, low amounts of phytoestrogens can protect against various cancers such as prostate, breast, bowel, and other cancers (Adlercreutz, 2002;Zhao and Mu, 2011). Moreover, soy isoflavones, including genistein and daidzein, can protect neurons in animal models of ALS, stroke, chronic sciatic nerve injury, and PD (Trieu and Uckun, 1999;Liu et al, 2008;Valsecchi et al, 2008;Chinta et al, 2013). Interestingly, findings suggest that soy isoflavones can improve cognitive function in postmenopausal women (Kritz-Silverstein et al, 2003).…”
Section: B Environmental Toxicantsmentioning
confidence: 99%